Does Blindness Boost Working Memory? A Natural Experiment and Cross-Cultural Study - Rindermann, Heiner; Ackermann, A. Laura; te Nijenhuis, Jan (Frontiers in Psychology, 2020)
Intelligence requires sufficient working-memory capacity. Traditionally, working memory was seen as a process and as a prerequisite for fluid intelligence. Working memory was assumed to be determined by maturation and health. There is a gap in the literature: It is still not fully understood to which extent and how working memory can be influenced. So this study tested how visual impairment and the extent of visual impairment are related to working memory capacity. In our study we compared N = 249 children (6–16 years) with and without visual impairment (blind, visually-impaired, sighted) in two countries (South Africa and Austria) at different development levels on their working-memory capacity and verbal comprehension. Using the WISC-IV, blind and visually-impaired children showed higher working-memory capacity than sighted children (r = +.35, 14 and 3 IQ points, respectively). On the other hand, visually-impaired children showed a weakness in verbal comprehension (r = −.39, on average 13 IQ points lower). The pattern remained robust when SES and race-ethnicity were controlled. Our natural (quasi-)experiment shows a pattern, which is unlikely to be genetic, and so supports the view that working memory and intelligence scores can be modified.